TRANSLATION ANALYSIS OF MECHANICAL ENGINEERING TERMS IN SCHAUM'S OUTLINES OF THEORY AND PROBLEMS OF HEAT TRANSFER - Yashinta Farahsani; Margaretha Dharmayanti Harmanto; Hana Nimashita; Agwin Degaf; Latif Amrullah (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2022)
Translation frequently conveys information about culture, knowledge, and other social interactions. It is also considered from the perspective of intercultural communication access to developments in the humanities, sciences, and technologies. It is the fastest, most effective, and most efficient approach to transmitting knowledge and technology. Therefore, it is necessary to apply translation methodologies and techniques to ascertain the translator's translation ideology. The research method used in this research is the qualitative research design. This research took samples of the translation of mechanical engineering terms in Schaum's Outline of Theory and Problems of Heat Transfer to look for techniques, methods, and ideologies used by translators to translate these terms from English into Indonesian. The data obtained were 175, with the discovery of 109 single translation techniques, 50 double translation techniques, and six triplet translation techniques. Three translation methods are applied: the literal translation method, the faithful translation method, and the semantic translation method. From the technical data and translation methods, the researcher concludes that the ideology applied by the translator is the ideology of foreignization.